Biotechnology Growth Partnership: A Potential Flagship Program in S&T - Adhikari, Raju; Adhikari, Benu (Nepal Journal of Biotechnology, 2010)
Nepal Journal of Biotechnology. Jan. 2011, Vol. 1, No. 1 : 55-58